Macroscale Superlubricity Accomplished by Sb2O3-MSH/C Under High Temperature - Gao, Kai; Wang, Bin; Shirani, Asghar; Chang, Qiuying; Berman, Diana (Frontiers in Chemistry, 2021)
Here, we report the high-temperature superlubricity phenomenon accomplished in coatings produced by burnishing powders of antimony trioxide (Sb2O3) and magnesium silicate hydroxide coated with carbon (MSH/C) onto the nickel superalloy substrate. The tribological analysis performed in an open-air experimental setup revealed that with the increase of testing temperature, the coefficient of friction (COF) of the coating gradually decreases, finally reaching the superlubricity regime (the COF of 0.008) at 300°C. The analysis of worn surfaces using in-situ Raman spectroscopy suggested the synergistic effect of the inner Sb2O3 adhesion layer and the top MSH/C layer, which do not only isolate the substrate from the direct exposure to sliding but also protect it from oxidation. The cross-sectional transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) results indicated the tribochemically-activated formation of an amorphous carbon layer on the surface of the coating during sliding. Formation of the film enables the high-temperature macroscale superlubricity behavior of the material system.